(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article discusses the interpretation of the ancient Lazgi melody on the stage of the puppet theater through puppets, highlighting the harmony of music with events and events in the puppet theater, as well as the professional performance of the director and actors. given.